RELAÇÃO DOS DISTÚRBIOS RESPIRATÓRIOS DO SONO ASSOCIADO AO DESENVOLVIMENTO DAS MALOCLUSÕES: REVISÃO DE LITERATURA - Martins Carneiro, Grace Kelly; Costa Rodrigues, Marcelo; Ferreira Araujo, Winicius Arildo; Dório Neves, Ayla Cristina; Alves Ferreira, Lícia Paula (REVISTA SAÚDE MULTIDISCIPLINAR, 2021)
Respiratory sleep disorders are characterized by partial or total obstruction of the air flow that goes to the lungs during sleep which is related to dental and skeletal malocclusion and causes changes in the development of the facial pattern, becoming the patient an oral respirator. The objective of the study was to verify the relationship of sleep-disordered breathing associated with the development of malocclusion, highlighting the importance of carrying out treatment with a multidisciplinary team. The method chosen for this study was the literature review. Therefore, searches were performed, articles in English and Portuguese and the databases were searched using the literature indexed on the Scientific Electronic Electronic Library Online (SCIELO) periodicals portal, in the Medical Literature Analyzes and Retrieval system databases online ( MEDLINE), Latin American and Caribbean Literature in Health Sciences (LILACS) and in Health Sciences Descriptors (DeCs) with the keywords: Malocclusion, snoring, mouth breathing, apnea. A bibliographic survey on the theme was made between the years of 1907 and 2020. Bibliographies containing the descriptors were included and, excluding, those that did not attempt to the theme or that were not available in the full version were included. A literature review was carried out, developed following the precepts of a descriptive study, through bibliographic research divided into stages. We conclude that there is an association between sleep-disordered breathing and malocclusions and that the multidisciplinary approach is fundamentally important for the treatment.